Spatiotemporal and Functional Behavior of Airway Dendritic Cells Visualized by Two-Photon Microscopy - Zoltán Veres, Tibor (American Society for Investigative Pathology, 2011)
Airway mucosal dendritic cells (DCs), located beneath the epithelium of the conducting airways, are believed to be specialized for immunosurveillance via sampling of antigens from the airway luminal surface. However, the dynamics of airway DC activity has not yet been visualized. We used two-photon microscopy to illuminate the endogenous mucosal DC network in the airways of mice. To characterize DC behavior, we used lung section preparations and an intravital microscopic approach. DCs displayed a heterogeneous movement pattern according to their localization within the airway mucosa: sessile intraepithelial DCs with a dendritiform shape exhibited active probing movements and occasionally formed transepithelial extensions into the airway lumen. In contrast, DCs within the deeper layers of the mucosal tissue migrated fast in an amoeboid manner, without probing movements, and slowed down after aeroallergen challenge. Strikingly, neither of these two mucosal DC populations ingested fluorescently labeled antigens after antigen administration to the airways in the steady state, in contrast to alveolar macrophage/DC populations in the lung periphery. Our results provide a first description of the dynamic behavior of airway mucosal DCs, with their exact role in antigen sampling remaining unclear.